Exploring the host-parasite relationship between brown kiwi (Apteryx mantelli), kiwi ticks (Ixodes anatis) and kiwi tick-borne haemoparasites : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Conservation Biology at Massey University, Manawatu, New Zealand - Bansal, Natasha (Massey University, 2020)
Host and parasites have co-evolved for millions of years providing selection pressures with the parasite using the host for survival and reproduction, and the host, in turn, developing defence strategies to combat the parasites to better survive infection. North Island Brown Kiwi (NIBK, 𝘈𝘱𝘵𝘦𝘳𝘺𝘹 𝘮𝘢𝘯𝘵𝘦𝘭𝘭𝘪), a species of ratite endemic to New Zealand, is host to a number of host-specific parasites, one of which is the Kiwi tick 𝘐𝘹𝘰𝘥𝘦𝘴 𝘢𝘯𝘢𝘵𝘪𝘴. Like the NIBK, the kiwi tick is also endemic and therefore vulnerable to extinction. The aim of this thesis was to fathom the host-parasite relationship between the NIBK and their ticks, as almost nothing is known about this relationship. To study any host-parasite relationship, we need to know basic life history traits of both parasites and hosts. As a result, this thesis combined laboratory and field methods to determine aspects of the tick life cycle, and field methods that determined various haematological and biochemical parameters of NIBK and how to use them to ascertain the effect of heavy tick loads on the birds. We also used various different laboratory methods to determine if these ticks were vectors to protozoa that might affect NIBK. We measured moulting and oviposition times of various stages of engorged kiwi ticks collected from NIBK and kept at various temperature and relative humidity (RH) regimes. We found that engorged larval and nymphal stages of 𝘐. 𝘢𝘯𝘢𝘵𝘪𝘴 preferred lower temperatures as compared to most other species of ixodid ticks with successful development occurring under RH above 94%, and temperatures of 10 to 20˚C. Whereas, in the field the different stages of the ticks were able to develop at drier humidity of 65% to 69%, under similar temperatures. We also found that the ticks were abundant in kiwi burrows throughout the year and prefer more tree and soil burrows in the forest. Using this, we were able to hypothesise a seasonal life cycle for the kiwi tick. Before we could look at the effect of these ticks on their NIBK host, we established a method of estimating tick infestations on the birds. Along with this, we also established normal reference range for haematological and biochemical values using different populations of NIBK. The results of both the tick index and the normal parameters can be used by managers and veterinarians around NZ when determining kiwi health. We then proceeded to remove/reduce tick infestation levels from a group of NIBK treated with parasiticides and compared their haematological and biochemical parameters with a group of untreated control birds. The treated birds showed higher total protein values and had a higher weight gain after reduction of tick infestation with recorded lower activity than control birds leading us to conclude that the ticks negatively affected the birds. However, when the birds were left untreated for a year, they gained those ticks back and their parameters went back to values prior to experimental removal of ticks. This indicated a co-evolutionary relationship between the NIBK and the kiwi tick, I. anatis, as in cases of chronic infection of a parasite on its host, especially when they co-evolve together, the costs of parasitism are not as pronounced as both host and parasite are in an arms race to increase their fitness. However, we found no evidence of tick borne protozoa in any of our infected birds, suggesting that either the infections were not present, present in extremely low intensities in the blood or we need more detailed investigations into what happened to the NIBK and tick specific haematozoa that have been previously reported in NIBK. This research contributed to our knowledge of the relationship between NIBK and the kiwi tick 𝘐. 𝘢𝘯𝘢𝘵𝘪𝘴. In the process, it also helped establish various protocols for assessing health of NIBK as well as assessing tick infestation on ground birds that can be used by a large group of individuals, including future researchers. As a result of this thesis, we recommend that wildlife managers also take parasite conservation and translocation into consideration while managing endemic host-parasite networks.
Keywords: North Island brown kiwi; Parasites; Ixodes; Tick-borne diseases in animals; New Zealand; 310407 Host-parasite interactions